Difference between Salivary pH Before and After Rinsing with White and Green Tea Solution - Dahniar Rizki Fahriani; Widia Susanti; Pradipto Subiyantoro (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2016)
Introduction: White and green tea contains Epigalocathechin-3-Gallate (EGCG) which is reported has bacteriostatic and bactericidal activity, thereby reducing the production of acid. White tea also has myricetin triglycoside compounds which is has antimicrobial effect and not found in the other types of tea. This study aims to determine whether there are differences in salivary pH before and after rinsing with white and green tea solution. Methods: This research was a quasi experimental with the pretest and posttest without control group design type. The samples were 34 people of medical students of UNS batch 2012-2014 chosen by purposive quota sampling technique. The samples were divided by simple random sampling technique into 2 groups, ie white tea group and green tea group. Every sample was taken out their saliva in the morning and early salivary pH was measured, then the first group rinsing with 20 ml white tea solution for 60 seconds and second group rinsing with 20 ml green tea solution for 60 seconds. After that, saliva was taken out again and measured as the final salivary pH. The collected data were analyzed with statistical Two Way (Within-Between) ANOVA test, the difference would be significant if p < 0.05. Results: This research showed that there were significant differences between salivary pH before and after each treatment group with the rinsing of white or green tea solution (p < 0.000). Differences in salivary pH before and after rinsing between white tea group and green tea group showed no significant difference (p = 0.981). Conclusion: Rinsing with white and green tea solution could increase salivary pH equally. Keywords: salivary pH, white tea, green tea, rinsing